Biosignature preparation for ocean worlds (BioPOW) instrument prototype - Duval, Korine A.; Van Volkenburg, Tessa B.; Craft, Kathleen L.; Person, Chanel M.; Harshman, John S.; Fernandes, Diarny O.; Benzing, Jennifer S.; McDowell, Emil G.; Nelson, Tyler W.; Divakar, Gautham S.; Pochettino, Owen M.; Perry, Mark E.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
In situ sampling missions to detect biosignatures on ocean worlds requires thorough sample preparation to manage the expected chemical complexity of such environments. Proposed instruments must be capable of automatic liquid sample handling to ensure sensitive and accurate detections of biosignatures, regardless of the initial chemical composition. Herein, we outline the design, build, and test of the integrated Biosignature Preparation for Ocean Worlds (BioPOW) system capable of purifying amino acids from icy samples. This four step modular instrument (1) melts ice samples, (2) purifies amino acids via cation exchange chromatography, (3) concentrates via vacuum drying, and (4) derivatizes amino acids to volatilize and enable detection with downstream analytical instruments. Initial experiments validated the thermal performance of the system by melting ice in the sample cup (1 mL sample, 3 °C to 28 °C, <5 minutes, 1.4 kJ) and heating the derivatization tank past the concentration temperature (20 °C to 60 °C, 12 minutes, 3.6 kJ) to the derivatization temperature (60 °C to 90 °C, 25 minutes, 7.5 kJ). Later experiments investigated important factors for automatic cation exchange using a design of experiments approach, and found that initial salt concentration, sample and eluate flow rates, and water wash volumes all play significant roles in reducing conductivity (1.1 x – 6.7 x) while maintaining phenylalanine yields between 31 and 94%. The modules were then integrated into a 12 cm x 20 cm x 20 cm fieldable platform for analysis, and the maturation of this design for future spaceflight is discussed.